Analisis Isi Mengenai Ketidakadilan Gender Dalam Film “ YUNI ” (2021) - Arfian Suryasuciramdhan; Hurul Aini; Hana Apriyanti; Nasywa Hasna Nabilla; Reva Sila Kinaya (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
The film Yuni tells the story of the struggle of a woman who wants to break gender stereotypes to gain the rights and freedom to choose for herself. By using Serang Javanese, Sundanese and Indonesian, this film attracts the attention of the audience. Yuni is a high school teenager who lives in a small town who has dreams of going to college after graduating from school. Yuni really likes the color purple. She is also a smart student at her school. With the support of a female teacher at her school, she is very enthusiastic about wanting to took a scholarship to go to college, but this desire was hindered by the environment around him which still held strong eastern culture and he was pressured to marry immediately after graduating from school. This research is a qualitative descriptive study that uses the film Yuni 2021 to present facts about inequality and the meaning of gender that were discovered at that time. The aim of the research is to describe and analyze phenomena and other social activities. This research takes a qualitative approach with its methodology. This research aims to determine the gender equality found in the film Yuni. The results of the analysis that the author presents are connecting the scenes of each scan, then understanding the meaning of the signs contained in the film Yuni which consist of visual and audio: (1) women cannot go to high school (2) women cannot do whatever they want. Denotational meaning, the women represented in the film Yuni show that the role of women is always attached to the domestic realm, having limitations in movement, in education. The connotation meaning of women in the film Yuni shows that Yuni has the courage to make a decision within herself to have the same rights in obtaining the same education as men.